2017
DOI: 10.1186/s13063-016-1739-9
|View full text |Cite
|
Sign up to set email alerts
|

A fixed inhaled nitrous oxide/oxygen mixture as an analgesic for adult cancer patients with breakthrough pain: study protocol for a randomized controlled trial

Abstract: BackgroundThe management of breakthrough pain in cancer patients is always a challenge for medical professions. Occurring in 80% of cancer patients with advanced disease, breakthrough pain significantly decreases both patient’s and caregiver’s quality of life. The aim of this study is to assess the analgesic efficacy of a fixed inhaled nitrous oxide/oxygen mixture for adult cancer patients with breakthrough pain.Methods/designThis is a randomized, placebo-controlled, double-blind study; it will be conducted in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 47 publications
0
14
0
Order By: Relevance
“…The determination of its sample size was on the basis of preliminary experimental data collected in the Anorectal Department for 30 patients. and our previous studies involved burn-dressing and cancer breakthrough pain [15,24]. The data indicated that 55% of participants receiving premixed nitrous oxide/oxygen had a meaningful change in pain score (a drop at least one-third of pain score [25]) at T1 and T2, while 15% of patients receiving oxygen was.…”
Section: Sample Size Determinationmentioning
confidence: 76%
See 3 more Smart Citations
“…The determination of its sample size was on the basis of preliminary experimental data collected in the Anorectal Department for 30 patients. and our previous studies involved burn-dressing and cancer breakthrough pain [15,24]. The data indicated that 55% of participants receiving premixed nitrous oxide/oxygen had a meaningful change in pain score (a drop at least one-third of pain score [25]) at T1 and T2, while 15% of patients receiving oxygen was.…”
Section: Sample Size Determinationmentioning
confidence: 76%
“…The expert will not be involved in the recruitment, gas distribution, date collection. Then, the random numbers will be stored and sealed in a designated research office to ensure concealment [15]. In order to maintain a double-blind environment, nurses and researchers are blinded and not allowed to touch the random numbers unless they can put forward justifiable reason and get the approval from the project supervisor.…”
Section: Randomization Allocation Concealment and Blindingmentioning
confidence: 99%
See 2 more Smart Citations
“…The worst pain severity as the primary end-point measure is employed to estimate sample size in the current research according to previous studies on physical therapy for pediatric burn injury pain and dentalgia pain [19,24]. According to our previous study on breakthrough pain [26], we used a pilot trial to determine the sample size. Fourteen subjects recruited in May 2019 were invited to the pilot trial.…”
Section: Sample Size Determinationmentioning
confidence: 99%